Prevalence of Giardiasis in Children Attending Semi-urban Daycare Centres in Guatemala and Comparison of 3 Giardia Detection Tests (Journal of Health, Population and Nutrition, 2013)
Giardia intestinalis is an intestinal parasite widely prevalent in children attending daycare centres worldwide and has been associated with undernutrition. Stool samples from 48 Guatemalan children (aged 1.5-7 years) attending participating daycare centres were analyzed over five weeks for presence of Giardia intestinalis using light microscopy, ELISA, and rapid dipstick test. Giardia prevalence rates were 43.7% at Week 0 and 44.7% at Week 4, based on ELISA. Intensity, but not prevalence, of infection showed a trend toward decreased weight-for-age (1-tailed p=0.08). We believe that ELISA analysis of stool samples may be further adapted for measuring the intensity of infection in humans. J HEALTH POPUL NUTR 2013 Jun; 31(2): 290-293 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16394